Translation Errors of Health Program Students’ Abstract from Indoneisa into English - Eka Fanti Sulistiyaningsih; Regita Ika Wulandari (Journalistics: Journal of English Teaching and Applied Linguistics, 2024)
Translation is a process of substituting equivalent content from one language into another language without change the meaning of the sentence. The research aims to find out the types of translation errors of health program students’ abstract from Indonesia into English in one of University in Central Java. The research design of this research is descriptive qualitative. The result of this research shows that types of translation errors of health program students’ abstract from Indonesia into English in one of University in Central Java spelling (23%), punctuation (7,6%), capitalization (30,7%), word form/part of speech (15,3%), terminology (7,6%), too literal or word for word (7,6%), omission (7,6%). The frequently most dominant types of translation error is capitalization. It showed that the translation of students’ abstract of health program is still poor.